2007
DOI: 10.1103/physrevstab.10.060401
|View full text |Cite
|
Sign up to set email alerts
|

Different approach to pulsed high-voltage vacuum-insulation design

Abstract: A theoretical methodology promising improved design of vacuum insulation in high-voltage pulsedpower systems is described. It consists of shaping the electromagnetic fields within the system in such a way that charged particles which can in principle initiate vacuum surface breakdown are deflected away from the insulator surface, and secondary electrons, if emitted, are prevented from restriking the surface. Thus, vacuum surface breakdown is prevented before it is able to develop. Our methodology is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…The results of these experiments support our previous work [1][2][3] in that they show that a small amount of primary electrons produced near the CTJ is sufficient to produce vacuum insulator surface flashover if the electric field accelerates them along this surface. If conditions exist that sufficient plasma forms at the ATJ and there is sufficient time and power for it to expand, acquire the anode potential, and shorten the anode cathode gap, flashover may develop.…”
Section: -4supporting
confidence: 86%
See 1 more Smart Citation
“…The results of these experiments support our previous work [1][2][3] in that they show that a small amount of primary electrons produced near the CTJ is sufficient to produce vacuum insulator surface flashover if the electric field accelerates them along this surface. If conditions exist that sufficient plasma forms at the ATJ and there is sufficient time and power for it to expand, acquire the anode potential, and shorten the anode cathode gap, flashover may develop.…”
Section: -4supporting
confidence: 86%
“…We conjectured that by deflecting these primary electrons away from the insulator surface the breakdown properties of the vacuum insulator could be improved. 1 Since we assume that electrons are the most common breakdown initiators, our conjecture excluded anode triple junction (ATJ) initiation. Recently, 2 by measuring the flashover breakdown electric fields over various insulator arrangements using a conditioning method, we experimentally demonstrated that for high voltage pulses of a microsecond time scale duration, initiation is indeed predominantly at the cathode triple junction (CTJ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous studies with respect to flashover development, methods to improve the flashover threshold or increase the flashover voltage contain either a multipactor suppression or a field-optimization-reducing emission from the CTJ. While various researchers have capitalized on the refined secondary emission yield (SEY) [30,31] or external fields [32,33] to constrain the formation of the multipactor, methods including insulator shape redesign and structural modification near the CTJ have been employed as well to reduce the field near the CTJ [34,35]. Yet flashover can still occur even when the cathode field is significantly reduced, as reported in previous experiments [36][37][38][39][40], which seemingly contradicts the SEEA model.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 6, it was suggested that voltage holdoff will considerably improve if primary electrons are deflected away from impacting while at the same time secondary electrons are accelerated away from the insulator surface so these electrons cannot restrike. Such a scheme is made possible by appropriate design of the orientation of the electric and magnetic fields near the insulator surface.…”
Section: Introductionmentioning
confidence: 99%